Diagnosis of Cervical Erosion - Olimjonovna, Temirova Dilnoza (American Journal of Bioscience and Clinical Integrity, 2024)
One of the leading pathologies of the female reproductive system is cervical cancer, which ranks 4th among cancer diseases. According to WHO, in 2023 there were 570,000 new cases detected worldwide, and an increase in incidence was noted among the young female population aged 20–30 years. There is also a problem of insufficient oncological alertness among women in Uzbekistan. A significant part of cervical pathologies is a precancerous condition. Therefore, the identification of such diseases at the outpatient stage is the most important task of an obstetrician-gynecologist. Currently, effective screening of cervical pathology is based on a consistent set of examinations, including colposcopy, cytology and detection of human papillomavirus – HPV testing.